Tor forms a dimer through an N-terminal helical solenoid with a complex topology - Domagoj Baretić (Nature Portfolio, 2016)
The target of rapamycin (Tor) is a Ser/Thr protein kinase that regulates a wide range of anabolic and catabolic processes. Here the authors describe a sub-nanometer cryo-EM structure of a yeast Tor–Lst8 complex and propose an overall topology that differs from that previously suggested for mTORC1.